THE INFLUENCE OF SKILLS, PERSONALITY, AND COMMUNICATION STYLE OF THE MASTER OF CEREMONY ON AUDIENCE SATISFACTION IN FORMAL EVENTS AT PT. BANK PEMBANGUNAN DAERAH KALIMANTAN SELATAN (PERSERODA), HEAD OFFICE BANJARMASIN - Sanusi; Decky C. Kananto Lihu; Erny Fuji Astuti (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
The objectives of this study are as follows: 1) To determine whether the skills of the Master of Ceremony partially influence audience satisfaction in formal events at PT. Bank Pembangunan Daerah Kalimantan Selatan (Perseroda), Banjarmasin Head Office. 2) To determine whether the personality of the Master of Ceremony partially influences audience satisfaction in formal events at PT. Bank Pembangunan Daerah Kalimantan Selatan (Perseroda), Banjarmasin Head Office. 3) To determine whether the use of the Master of Ceremony communication style partially significantly influences audience satisfaction in formal events at PT. Bank Pembangunan Daerah Kalimantan Selatan (Perseroda), Banjarmasin Head Office. 4) To determine the skills, personality and use of the Master of Ceremony's communication style simultaneously have a significant influence on audience satisfaction in formal events at PT. Bank Pembangunan Daerah Kalimantan Selatan (Perseroda) Banjarmasin Head Office. This research is quantitative. The population in this study were customers who attended an event at PT. Bank Pembangunan Daerah Kalimantan Selatan (Perseroda) Banjarmasin Head Office in March 2025, totaling 100 priority customers. The sample in this study consisted of 54 priority customers. The sampling technique in this study used purposive sampling. Based on the research results, the following conclusions can be drawn: 1) The skills of the Master of Ceremony have a partial effect on audience satisfaction at formal events at PT. Bank Pembangunan Daerah Kalimantan Selatan (Perseroda) Banjarmasin Head Office. 2) The personality of the Master of Ceremony has a partial effect on audience satisfaction at formal events at PT. Bank Pembangunan Daerah Kalimantan Selatan (Perseroda) Banjarmasin Head Office. 3) The use of the Master of Ceremony's communication style has a partial effect on audience satisfaction at formal events at PT. Bank Pembangunan Daerah Kalimantan Selatan (Perseroda) Banjarmasin Head Office. 4) The skills, personality, and use of the Master of Ceremony's communication style have a simultaneous effect on audience satisfaction at formal events at PT. South Kalimantan Regional Development Bank (Perseroda), Banjarmasin Head Office. Leaders should integrate technical training, soft skills development, and communication workshops into employee development programs